(untitled) (Baština, 2020)
The collapse of socialism as a consequence of primarily economic inefficiency has raised in front of the post socialist countries the dilemma of choice (what a miracle) the path to capitalism. On this reversible, historical process, the leading Western countries have had a ready answer - the Washington Consensus. The strict implementation of the ten Washington reform economic policies conceived on the neoliberal doctrine led to the construction of the Anglo-Saxon development model of capitalism. The Washington narrative had the unreserved support in the measures and decisions of the International Monetary Fund and the World Bank, though it originally intended as a set of neo-liberal crisis solution measures in Latin American countries. The consistent implementation of the Washington Regulations with the shock therapy method has had mostly negative consequences for the economic growth and development of both the transition and Latin American countries. Countries that have approached economic reforms in a gradualistic manner, respecting national characteristics and interests, such as the "East Asian tigers", have as a rule achieved economically respectable growth and social well-being.